A horizontal flow biofilm reactor (HFBR) technology for the removal of methane and hydrogen sulphide at low temperatures - Kennelly, C (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
A novel horizontal flow biofilm reactor (HFBR) has been adapted and tested for its efficiency in treating hydrogen sulphide (H(2)S) and methane (CH(4)) gas. Six pilot-scale HFBR reactors were commissioned, three each treating CH(4) and H(2)S respectively. The reactors were operated at 10 °C, often typical of ambient temperatures in Ireland, and were simultaneously dosed with an air mixture containing the gas in question and with synthetic wastewater (SWW). Three reactors (HFBR 1, 2 and 3), treating an air mixture containing CH(4), were operated over three phases (Phases 1-3) lasting 180 days in total. During each phase the air mixture flow rate (AFR) and the plastic media top plan surface area (TPSA) loading rate to HFBR 1, 2 and 3 were 1.2 m(3)/m(3)/h and 0.6 m(3)/m(2) TPSA/h respectively. In Phase 1 the reactors were operated in triplicate and were loaded with 8.6 g CH(4)/m(3) reactor/h (4.3 g CH(4)/m(2) TPSA/h) and a synthetic wastewater (SWW) similar to domestic sewage at 10 °C. During Phase 2 (reactors also operated in triplicate) the effect of temperature on the reactor performance was examined. During Phase 3 the reactors were operated independently in order to examine the effects of omitting organic carbon and adding additional nitrogen in the form of nitrate-nitrogen (NO(3)-N), rather than ammonium-nitrogen (NH(4)-N). During Phase 3, CH(4) removal efficiencies (RE) of up to 92.8% were achieved at an empty bed retention time (EBRT) of 50 min, equating to a maximum removal of 8.0 g CH(4)/m(3) reactor/h. Three additional reactors (HFBR 4, 5 and 6) were used to treat an air mixture containing H(2)S and were loaded at an AFR of 15 m(3)/m(3) reactor/h (7.5 m(3)/m(2) TPSA/h) with an average H(2)S loading rate of 3.34 g H(2)S/m(3) reactor/h (1.67 g H(2)S/m(2) TPSA/h). After 50 days of operation, the RE reached 100% for all three reactors at an EBRT of 4 min. In each reactor, profile samples of biofilm, air and liquid were taken periodically from various regions of the HFBR. These allowed detailed description of removal processes and optimisation of the reactors by detailing changes in air, liquid and biofilm composition as air moved through the reactor